Zintegrowany system zarządzania ryzykiem - workflow - Gospodarek, Tadeusz (Integrated system of the risk management - workflow, 2006)
In this article the author presents the project of the workflow system of risk management, which was created for the firm Hutmen SA. There are presented terms connected with the organizational workflow for the three operational levels (Front Office, Middle Office and Back Office). The author also describes functional needs of the system which should make writing programmes that arc realizing rules of the hedging strategy easier. *
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 103-113